PELATIHAN PENGEMBANGAN DAN PENGEMASAN PERANGKAT PEMBELAJARAN BERDASARKAN KURIKULUM 2013 PADA GURU-GURU SEJARAH DI SMA/SMK KECAMATAN BULELENG. - Ketut Sedana Arta; Desak Made Oka Purnawati; I Wayan Putra Yasa; Tuty Maryati (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The main objective of this training is to increase the insight and skills of history teachers in Buleleng District in understanding the 2013 curriculum and the development and packaging of learning devices in accordance with the demands and needs of the 2013 curriculum. Thus, history teachers in Buleleng District have readiness and adequate ability to implement the 2013 curriculum in accordance with their nature. Training and mentoring for the development and packaging of this learning device will be carried out using two synergistic methods, namely: the method of training and class mentoring / supervision. The training method is used to increase knowledge and insight about the preparation and packaging of historical learning tools based on the 2013 curriculum and its assessment. While the classroom supervision method is used to evaluate the skills of history teachers in Buleleng District in implementing learning tools in their respective classes.